2015
DOI: 10.1016/j.stemcr.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes with Genetically Encoded Calcium and Voltage Fluorescent Reporters

Abstract: SummaryThe advent of the human-induced pluripotent stem cell (hiPSC) technology has transformed biomedical research, providing new tools for human disease modeling, drug development, and regenerative medicine. To fulfill its unique potential in the cardiovascular field, efficient methods should be developed for high-resolution, large-scale, long-term, and serial functional cellular phenotyping of hiPSC-derived cardiomyocytes (hiPSC-CMs). To achieve this goal, we combined the hiPSC technology with genetically e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
149
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(154 citation statements)
references
References 36 publications
5
149
0
Order By: Relevance
“…Subsequently, many hiPSC-CMs models of both CPVT types [20][21][22][23][24][25][26][27][28][29] were shown to recapitulate the clinical phenotype in the culture-dish by displaying abnormal Ca 2+ handling and arrhythmias. Here, we focused on CPVT2 and found, similar to previous reports, 24,25,29 21,30 We recently investigated this phenomenon in a CPVT1-hiPSC-CMs model demonstrating a reduced SOICR threshold in the affected cells. 21 Here, we demonstrated the ability to model SOICR also in the CPVT2-hiPSC-CMs and revealed that the D307H-CASQ2 may also reduce SOICR threshold in the affected cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, many hiPSC-CMs models of both CPVT types [20][21][22][23][24][25][26][27][28][29] were shown to recapitulate the clinical phenotype in the culture-dish by displaying abnormal Ca 2+ handling and arrhythmias. Here, we focused on CPVT2 and found, similar to previous reports, 24,25,29 21,30 We recently investigated this phenomenon in a CPVT1-hiPSC-CMs model demonstrating a reduced SOICR threshold in the affected cells. 21 Here, we demonstrated the ability to model SOICR also in the CPVT2-hiPSC-CMs and revealed that the D307H-CASQ2 may also reduce SOICR threshold in the affected cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In the cardiac field, hiPSCs were established from healthy individuals and from patients inflicted with acquired 9 and several types of inherited cardiac disorders. 10,11 Patient-specific hiPSC-derived cardiomyocyte (hiPSC-CM) models of different inherited arrhythmogenic syndromes (including the long-QT, [12][13][14][15] Brugada, 16 and sodium channel overlap 17 syndromes; arrhythmogenic right ventricular cardiomyopathy 18,19 ; and both types of CPVT [20][21][22][23][24][25][26][27][28][29] ) were…”
Section: See Editorial By LI Et Almentioning
confidence: 99%
See 3 more Smart Citations